A Water Stable Metal–Organic Framework with Optimal Features for CO2 Capture1. Issue 39 (20th June 2013) - Yang, Qingyuan; Vaesen, Sébastien; Ragon, Florence; Wiersum, Andrew D.; Wu, Dong; Lago, Ana; Devic, Thomas; Martineau, Charlotte; Taulelle, Francis; Llewellyn, Philip L.; Jobic, Hervé; Zhong, Chongli; et al.
<x xml:space="preserve">Abstract</x> One flue over the cuckoo's nest: A novel porous Zr‐based MOF combining a high chemical stability, easy "green" synthesis and scalability is prepared. This material incorporating carboxylic functions on its organic linkers has thermodynamically and kinetically very promising properties for CO2 capture from post‐combustion flue gas under real working conditions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>